2019
DOI: 10.2139/ssrn.3400674
|View full text |Cite
|
Sign up to set email alerts
|

Money Laundering and Corruption: Birds of a Feather Flock Together

Abstract: This paper is the first to analyse the three-way relationship among money laundering, antimoney-laundering efforts and corruption. On the one hand, if we assume that the goal of criminals involved in corruption is to minimize the probability of being detected, then corruption represents a demand for money laundering (trigger effect), while money laundering can serve as an effective way to clean the revenue from corruption for re-investment (multiplier effect). On the other hand, criminals can try to maximize t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…As Christensen (2011) and Barone et al (2019) have concluded, corruption generates demand for money laundering activities, while the possibility of laundering corruptly obtained money offers a supply-side stimulant for corrupt practices.…”
Section: Introductionmentioning
confidence: 99%
“…As Christensen (2011) and Barone et al (2019) have concluded, corruption generates demand for money laundering activities, while the possibility of laundering corruptly obtained money offers a supply-side stimulant for corrupt practices.…”
Section: Introductionmentioning
confidence: 99%